Multifunctional starch-based material for contaminated emulsions separation and purification. (1st October 2021) - Zhang, Fan; Chi, Hui; Wang, Chao; Wang, Xinyue; Wang, Yinchuan; Zhang, Hao; Xu, Kun; Bai, Yungang; Wang, Pixin
Abstract: Stable water-in-oil (W/O) emulsions can produce at many industrial production occasions. However, most materials for its separation have serious fouling problems. To overcome this shortcoming, we fabricated an easy cleaning multifunctional starch-based material with unique wetting behavior which could realize efficient separation and purification of W/O emulsions. This material has a hierarchical structure and superoleophilic and under oil superhydrophobic surfaces which could separate various W/O emulsions in a high separation efficiency and flux without external pressure. In addition, the decrease of separation flux was not observed for this material, which can be reused more than 10 times after washing with ethanol and drying after each separation cycle. Furthermore, this material also could realize efficient removal of dyes and heavy-metal and rare-earth ions simultaneously during a separation process. The material shows great potential for separating and purifying stable W/O emulsions produced during the industrial production. Graphical abstract: Unlabelled Image Highlights: An easy cleaning multifunctional starch-based material was fabricated. A hierarchical structure and unique wettability surfaces were obtained. W/O emulsions separation and purification could realize in one step. The mechanism for separation and purification was researched in detail.